Enactment of hands-on practical activities through using easily accessible resources in a Grade 10 Physical Science classroom - Ndevahoma, Martha Kashike (Rhodes University, Faculty of Education, Department of Education, 2020)
The Namibian National Subject Policy Guide for Physical Science Grade 8-12 (MoE, 2010) indicates that science teachers should be creative and innovative in producing their own teaching and learning support materials that are linked to practice. Practical activities play a major role in the learning of science. Due to the lack of science laboratory equipment, however, minimal practical activities are done in some schools especially under-resourced disadvantaged schools. It is against this background that this case study investigated the possibilities and challenges associated with the use of easily accessible resources to carry out hands-on practical activities. Underpinned by an interpretive paradigm, this study used a mixed-method approach by generating both quantitative and qualitative data. It was carried out in the Otjozondjupa region in Namibia at Wato Secondary School (pseudonym). It was conducted with a Grade 10 Physical Science class consisting of 30 learners. To generate data, questionnaires, focus group interviews, lesson observations, stimulated recall interviews, as well as learners' journal reflections were used. Conceptions, dispositions, interest and sense-making were used as conceptual lenses while Vygotsky's social constructivism was the theoretical framework that informed this study. Quantitative data were analysed using the conceptual lenses and were subsequently presented in tables and graphs. That is, a deductive approach to analysis was used. On the other hand, a thematic approach was used to analyse the qualitative data. That is, qualitative data were inductively analysed to come up with sub-themes and themes. The findings from this study revealed significant shifts in learners' conceptions, dispositions and interest towards science after the use of easily accessible resources to do hands-on practical activities. Similarly, learners' sense-making of science concepts improved. This study thus recommends that science teachers should, where possible, make use of easily accessible resources to carry out hands-on practical activities during their science lessons. During such hands-on practicals, however, emphasis should be on the development of scientific concepts.
Keywords: Physical science -- Study and teaching (Secondary) -- Namibia